A Simple Fluorescence Turn‐on Probe for the Detection of Hg2+ Ion in Aqueous Solution and Soil With AIE and ICT Mechanisms. (8th July 2020) - Hu, Danling; Liao, Sijie; Chen, Xue; Du, Jincao; Dawood, Kamran; Chauhan, Sachin; Gao, Chao; Li, Wei
Abstract : A novel fluorescent probe TSA for the high selectivity of mercury (Hg 2+ ) ion has been explored, which was obtained by two‐step synthesis. Probe TSA was barely emissive in HEPES buffer. In the presence of Hg 2+ ion, the dithioacetal unit in probe TSA was hydrolyzed to be formyl group, consequently causing the intense sky‐blue emission via aggregation‐induced emission and intramolecular charge transfer mechanisms. Moreover, probe TSA was potential to detect Hg 2+ ion in dyeing wastewater and clay soil. Abstract : A novel fluorescence turn‐on probe TSA for the detection of Hg 2+ ion in aqueous solution and clay soil by AIE and ICT mechanisms has been explored.